Production Costs, Promotion Costs, and Sales Volume to Net Profit in Pharmaceutical Sector Manufacturing Companies - Adnan Pratama, Ifanny; Aprilia Sari, Petty (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To identify and analyze the effect of production costs, promotion costs and sales volume on the company's profits for pharmaceutical companies listed on the IDX. Background Problems: he pharmaceutical industry is facing a moderately raised condition where the demand for pharmaceutical products related to the handling of Covid-19 is increasing, on the other hand the demand for products that are not directly related to Covid-19 has decreased. Novelty: Re-testing the same variables in previous research, in the Covid-19 Case Research Methode. Research Methods: Data collection techniques with certain considerations using purposive sampling at 9 pharmaceutical companies, using SPSS 25 as a test tool. Finding/Results: Production costs partially have no significant effect on net income, promotion costs and sales volume have a significant effect on net income. Conclusion: There is a need to reduce production costs to a minimum in order to maintain profits and increase promotions and sales volume in pharmaceutical companies, especially during the Covid-19 pandemic.